2017
DOI: 10.1017/s014271641700008x
|View full text |Cite
|
Sign up to set email alerts
|

Prominence of gender cues in the assignment of thematic roles in German

Abstract: Two eye-tracking experiments examined influences of grammatical and stereotypical gender cues on the assignment of thematic roles in German. Participants (N1 = 32, N2 = 40) read sentences with subject- and object-extracted relative clauses, where thematic agents and patients remained ambiguous until the end of the relative clause. The results reveal a linguistic gender bias: agent roles are assigned more easily to grammatically masculine than feminine role nouns and stereotypically neutral than female ones. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…Targets of higher prominence (such as a person or an animate target) are seen to more probably occupy the position of agent than of the recipient of an action. Importantly, eye-tracking studies have shown that masculine rather than feminine role nouns are expected to serve as thematic agents in a sentence (Esaulova et al, 2014(Esaulova et al, , 2017.…”
Section: Grammatical Prominencementioning
confidence: 99%
“…Targets of higher prominence (such as a person or an animate target) are seen to more probably occupy the position of agent than of the recipient of an action. Importantly, eye-tracking studies have shown that masculine rather than feminine role nouns are expected to serve as thematic agents in a sentence (Esaulova et al, 2014(Esaulova et al, , 2017.…”
Section: Grammatical Prominencementioning
confidence: 99%
“…Studies conducted regarding natural gender languages as well as grammatical gender languages show that the use of masculine-only forms actually leads to a male bias in mental representation, irrespective of the methods used (for example, see Esaulova, Reali, & von Stockhausen, 2017; Gabriel, Gygax, Sarrasin, Garnham, & Oakhill, 2008; Gygax, Gabriel, Sarrasin, Oakhill, & Garnham, 2008; Sato, Gabriel, & Gygax, 2016; Sato, Gygax, & Gabriel, 2016).…”
Section: Psychological and Social Correlates Of The Distinction Of Th...mentioning
confidence: 99%
“…Studies conducted regarding natural gender languages as well as grammatical gender languages show that the use of masculine-only forms actually leads to a male bias in mental representation, irrespective of the methods used (for example, see Esaulova, Reali, & von Stockhausen, 2017;.…”
mentioning
confidence: 99%
“…Ferreira ( 2003 ), for instance, reported that participants made more mistakes when they were asked to identify agents and patients in passive sentences where the patient was realized as the subject compared to active sentences where the agent was the subject. Similarly, relative clauses that start with a patient (object-extracted relative clauses, such as Die Studenten, die die Fahrradfahrerin übersehen hat, sind verletzt ‘The students, whom the cyclist overlooked, are hurt’) are reported as more difficult for comprehension than those that start with an agent (subject-extracted relative clauses, such as Die Studenten, die die Fahrradfahrerin übersehen haben, sind verletzt ‘The students, who overlooked the cyclist, are hurt’) (e.g., Friederici et al 1998 ; Gordon et al 2001 ; Staub 2010 ; Esaulova et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%